2004
DOI: 10.1007/s11837-004-0131-5
|View full text |Cite
|
Sign up to set email alerts
|

Powder metallurgy Ti-6Al-4V-xB alloys: Processing, microstructure, and properties

Abstract: This article describes processing of Ti-6Al-4V-xB alloys via pre-alloyed and blended elemental powder metallurgy techniques. The infl uence of processing on the microstructural evolution and mechanical properties of the alloys produced by these two routes is summarized, and the thermo-mechanical response and optimization of processing parameters to produce defect-free engineering shapes in these alloys is also discussed. Potential applications and issues involved in the development of these materials for damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…4(d)] was indexed during the EBSD experiments and no TiB 2 was observed in the Ti-6Al-4V-0.5B alloy. This is in agreement with thermodynamic expectations [17,[21][22][23][24] and with the Feng et al [20] statement.…”
Section: Microstructure Morphologysupporting
confidence: 93%
“…4(d)] was indexed during the EBSD experiments and no TiB 2 was observed in the Ti-6Al-4V-0.5B alloy. This is in agreement with thermodynamic expectations [17,[21][22][23][24] and with the Feng et al [20] statement.…”
Section: Microstructure Morphologysupporting
confidence: 93%
“…3,4 These advances have signifi cant implications for the development of next-generation high-performance TMC materials. The higher strength and stiffness of these alloys is expected to improve transverse properties and, therefore, reduce anisotropy in TMCs.…”
Section: Titanium Composite Materials and Processesmentioning
confidence: 99%
“…Further, P/M processing produces a small number of large primary TiB particles that limit tensile elongation. 4 For the best balance of mechanical properties, these need to be eliminated.…”
Section: Merging Technologies: the Challengementioning
confidence: 99%
“…On the other hand, Ti-6Al-4V alloy has poor workability and the fabrication cost of complex components by machining is significantly high [1][2][3][4][5][6] . Therefore, metal injection molding (MIM) process is hoped to reduce the productive cost of such complex parts.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the addition of a small quantity of boron to this alloy has resulted refining the grain size of the lamellar microstructure [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%